2015
DOI: 10.1016/j.jval.2015.09.283
|View full text |Cite
|
Sign up to set email alerts
|

Diagnoses And Treatment Patterns For Non-Small Cell Lung Cancer (Nsclc) Within The Private Health System In Brazil

Abstract: A825oncologic products within Latin America (LA) in comparison to a developed market (Canada). Methods: A panel of opinion leaders and policy-makers from Brazil, Colombia, Argentina, Mexico, and Canada was convened to understand current challenges in health care, patient access, and reimbursement of high-cost oncologic products with a focus on NSCLC. Results: In LA, patient access to biomarker testing in all cancers is limited, except for common biomarkers like HER2 in breast cancer. In Canada, there is no uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
5

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
1
0
5
Order By: Relevance
“…Therefore, knowledge has to be constructed from the results of retrospective studies (5). Bone metastasis identified at the initial diagnosis of NSCLC typically indicates the possibility of consequent tumor spread and a poor patient prognosis (15). Decroisette et al (16) reported a poor prognosis among NSCLC patients exhibiting bone metastatic disease.…”
Section: A B Discussionmentioning
confidence: 99%
“…Therefore, knowledge has to be constructed from the results of retrospective studies (5). Bone metastasis identified at the initial diagnosis of NSCLC typically indicates the possibility of consequent tumor spread and a poor patient prognosis (15). Decroisette et al (16) reported a poor prognosis among NSCLC patients exhibiting bone metastatic disease.…”
Section: A B Discussionmentioning
confidence: 99%
“…Além disso, a amostra é semelhante às publicadas em estudos anteriores, que incluíam pacientes de instituições públicas ( Martins & Pereira, 1999;Barros et al, 2006), privadas (Araujo et al, 2014;Younes et al, 1992) e de ambos os serviços de saúde (de Castro et al, 2017). Em relação à histologia, os achados divergem da literatura publicada até 2005 no Brasil (Martins & Pereira, 1999;Barros et al, 2006;Younes et al, 2004) e estão alinhados com os estudos publicados mais recentemente (Araujo et al, 2014;de Castro et al, 2017;Lopes et al, 2015), com a histologia não escamosa sendo a mais prevalente na literatura do país.…”
Section: Discussionunclassified
“…A maioria dos pacientes (76,3%) foi testada para biomarcadores, percentual maior do que o observado nos Estados Unidos (Pan et al, 2013), Austrália, Alemanha e Itália, semelhante ao observado na Espanha, Coreia e inferior ao relatado em Taiwan (de Castro et al, 2017). Essa taxa também é maior que as taxas relatadas por outros estudos brasileiros sobre CPNPC (de Castro et al, 2017;Lopes et al, 2015). Essa diferença pode ser devida ao viés de seleção das instituições incluídas no estudo, já que todos são centros de oncologia de referência do sistema saúde privado do Brasil.…”
Section: Discussionunclassified
See 2 more Smart Citations